An Optical Fiber Twist Sensor With Temperature Compensation Mechanism Based on T-SMS Structure - Yujian Li; Ping Lu; Zhiyuan Qu; Wei Zhang; Wenjun Ni; Deming Liu; Jiangshan Zhang (IEEE Photonics Journal, 2020)
A new optical fiber twist sensor with temperature compensation mechanism is designed and experimentally demonstrated. The main structure of this twist sensor is a torsion perturbation point cascaded with single mode-multimode-single mode (SMS) fiber structure. The experimental results show that the twist sensor has ability to distinguish the twist direction with sensitivities of 9.5 pm/° and 34.7 pm/° at the chosen dips in the range from -100° (CCW) to 140° (CW). Furthermore, the temperature response characteristic of the sensor is also researched through experiment. Temperature sensitivities of 71.8 pm/°C and 65.2 pm/°C can be obtained at the same dips in the range from 20 °C to 75 °C. In addition, the temperature's influence can be compensated with post-measurement calculation through the cross-matrix. The theoretical resolutions of twist and temperature simultaneous measurement are ±0.084° and ±0.32 °C, respectively.